(NtIPOMORFIZM MINERALOW (B:s (NsPRAWO^NIK (B/s - (NgINZBURG(B, (Na(B.(Ni(B. s; (N~ERNY[EWA(B, (NlIDIQ wASILXEWNAs; (NkUPRIQNOWA(B, (NiRINA iWANOWNAs; (N~ERNY[EWA(B, (NlIDIQ wASILXEWNAs ((NmOSKWA (B:s (NnEDRA(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE RAZDELOWs
Keywords: (NmINERALYs; (NtIPOMORFNYE SWOJSTWAs